2010
DOI: 10.1515/advgeom.2010.031
|View full text |Cite
|
Sign up to set email alerts
|

Rank four vector bundles without theta divisor over a curve of genus two

Abstract: We show that the locus of stable rank four vector bundles without theta divisor over a smooth projective curve of genus two is in canonical bijection with the set of theta-characteristics. We give several descriptions of these bundles and compute the degree of the rational theta map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Notably, θ is an embedding for r = 2 [27], [10], [21] and it is a morphism when r = 3 for g ≤ 3 and for a general curve of genus g > 3, [4], [36]. Finally, θ is generically finite for g = 2 [4], [11] and we know its degree for r ≤ 4, [25], [35]. There are also good descriptions of the image of θ for r = 2 g = 2, 3 [28] [34], r = 3, g = 2 [31] [29], r = 2, g = 4 [33].…”
Section: The Theta Mapmentioning
confidence: 99%
“…Notably, θ is an embedding for r = 2 [27], [10], [21] and it is a morphism when r = 3 for g ≤ 3 and for a general curve of genus g > 3, [4], [36]. Finally, θ is generically finite for g = 2 [4], [11] and we know its degree for r ≤ 4, [25], [35]. There are also good descriptions of the image of θ for r = 2 g = 2, 3 [28] [34], r = 3, g = 2 [31] [29], r = 2, g = 4 [33].…”
Section: The Theta Mapmentioning
confidence: 99%
“…Moreover, the indeterminacy locus of D consists of those bundles V ∈ SU C (r ) for which (1) is the whole Picard variety. This has been much studied; see for example Pauly [Pau10], Popa [Pop99] and Raynaud [Ray82]. Brivio and Verra [BV12] showed that D is generically injective for a general curve of genus g ≥ 3r r − 2r − 1, partially answering a conjecture of Beauville [Bea06,§6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the indeterminacy locus of consists of those bundles for which (1) is the whole Picard variety. This has been much studied; see, for example, Pauly [Pau10], Popa [Pop99] and Raynaud [Ray82].…”
Section: Introductionmentioning
confidence: 99%